PEMBELAJARAN BAHASA ARAB PADA ANAK USIA DINI UNTUK MEMAHAMI AL-QUR’AN - Aziz Muzayin; Meitia Faramida Sugiharyati (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
Early childhood education is an asset and capital and provision in reading and developing the potential, intelligence and learning styles of early childhood. In addition, in practice, all components and devices that can maximize a child's potential must be actualized. The method in this study is descriptive which describes the Arabic language teaching carried out in order to achieve goals. The teaching objectives are formulated in such a way that the teaching objectives are achieved properly. the method is determined by many factors, including teaching objectives, language background of the learner, age of the learner, available time, teacher readiness, and socio-cultural factors. Various methods used in learning Arabic are Singing, Reading and Memorizing methods.